The secret of Nightingale Wood - Strange, Lucy (Chicken House, 2019)
With her father working abroad, her mother ill, and Nanny Jane too busy, Henrietta "Henry" uncovers the secrets of their new home Hope House, but when she ventures into Nightingale Wood, she finds something that changes her whole world.